The Impact of Translanguaging Strategies on Students’ Speaking Confidence - Muhammad Toza Dwi Wahyudi; Hefy Sulistyawati (Continuous Education: Journal of Science and Research, 2026)
This study examines the conflict between monolingual teaching policies and the multilingual realities found in Indonesian EFL classrooms. It explores how translanguaging strategies influence students’ confidence in speaking English. The objectives are to identify the types of translanguaging practices used by teachers to support students’ confidence and to examine their impact on learners’ perceived speaking ability, anxiety levels, and willingness to communicate. A qualitative research design with a single instrumental case study approach was applied. The study was conducted in an eleventh-grade class in Surakarta, involving one teacher and three selected students through purposive sampling. Data were obtained through classroom observations and in-depth interviews, then analyzed using the interactive model of data condensation, data display, and conclusion drawing and verification. The findings indicate that the teacher frequently alternated between English and Indonesian to explain difficult grammar points, clarify misunderstandings, and provide corrective feedback during speaking activities. These translanguaging practices contributed positively to students’ learning by improving comprehension, strengthening perceived speaking competence, lowering anxiety, and increasing participation in oral communication. However, the extent of these effects differed among students depending on their proficiency levels and emotional readiness. Overall, the study suggests that flexible language use is more effective than strict monolingual instruction in supporting students’ psychological readiness and confidence in speaking English, thereby enhancing classroom interaction and communicative engagement.